SOCIAL MEDIA AS ENVIRONMENTAL STIMULUS: HOW eWOM, SOCIAL MEDIA INFLUENCE, AND REVIEWS SHAPE THAI TOURISTS’ MEMORABLE EXPERIENCES, DESTINATION TRUST, SUBJECTIVE WELL-BEING, AND VISIT INTENTIONS TO ECOTOURISM DESTINATIONS - Shoosanuk, Ampon; Kornsuphkit, Thanat; Shoosanuk, Chaveewan; Chenchan, Suthisa; Mataac, Chito (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2025)
Introduction: This study examines the factors that influence memorable experiences, destination trust, subjective well-being, and visit intention among tourists at ecotourism destinations in Thailand. Digital communication channels increasingly influence tourist decision-making and experience formation in contemporary tourism contexts. Objective: To examine how electronic word-of-mouth (eWOM), social media influence, and social media reviews affect memorable tourism experiences; how these factors influence destination trust; and the impact of memorable experiences and destination trust on subjective well-being and visit intention. Methods: A quantitative approach was employed, collecting data through electronic and traditional questionnaires from 499 tourists using quota sampling. Structural equation modeling was utilized to test the hypothesized relationships between variables. Results: eWOM, social media influence, and social media reviews demonstrated positive impacts on memorable experiences. These factors, together with memorable experiences, significantly enhanced destination trust. Both memorable experiences and destination trust positively influenced tourists’ subjective well-being and visit intention, confirming the proposed relationships. Conclusion: Digital communication channels significantly shape tourist experiences, trust formation, and subsequent well-being and visit intentions in ecotourism contexts. These findings provide valuable insights for destination management and marketing strategies in the digital age.